Acculturation and Linguistic Factors on International Students’ Self-Esteem and Language Confidence - Lopez, Iris Y.; Bui, Ngoc H. (Journal of International Students, 2014)
Acculturation and linguistic factors were examined as predictors of self-esteem and language confidence among 91 international college students. The majority of participants were Asian (64.8%), female (59.3%), and graduate students (76.9%). Assimilative (adopting host cultural values) and integrative (blending both host and home cultural values) modes of acculturation, less frequency of contact with host culture members, and lower quality of contact predicted higher self-esteem. Less social support and lower English language confidence also predicted higher self-esteem. Also, higher self-esteem was positively related to greater perceived daily hassles (minor stressors faced by students). Furthermore, longer length of stay and greater assimilation and integration scores significantly predicted greater English language confidence. Limitations and implications for international students and educational institutions are discussed.